MEMPELAJARI PROSES ERUPSI GUNUNG BERAPI MELALUI EKSPERIMEN - Intan Fadhila; Nazwa Azahra; Dwi Rara Amiati (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to test the effectiveness of a volcanic eruption simulation using a simple chemical reaction (baking soda and vinegar) in improving students' understanding of the concept of volcanic eruption and their science process skills. The study used a qualitative descriptive approach with an exploratory practicum. This study did not use statistical population and sample sizes, as all activities were conducted within a single student group, acting as both implementers and observers. The data sources in this study were primary data obtained directly from observations during the practicum activities. Data collection instruments included observation sheets (direct observation), photographic documentation, and notes from experiments and group discussions. Based on the research results, it was found that the volcanic eruption simulation using simple materials (baking soda and vinegar) was very effective in clarifying understanding of the basic concept of volcanic eruption, making it suitable for widespread application in science education, particularly at the elementary level and in prospective teacher training.